Developing a Software Mechanism for Scheduling and Tracking Project Lifecycle Using Open-Source Software: An application on a government institution - Osman Abd allah Nasr Ali (Universitas Bina Darma, 2020)
This research aims at developing a software mechanism for scheduling and tracking the status of pre-planned tasks using an open sources to achieve projects in government institutions based on project management theory. This mechanism will facilitate the system process via planning, managing, and evaluating the project team activities to ensure that the project is running according to the time and financial plans. The system will also enables the work team to share tasks information, and follow their status during the lifecycle of these tasks. The system will also allow the project management to benefit from these reports to continuously assess individuals, tasks, and refine management decisions for present and future projects. The study is also relied on an open source project management software (ODOO) in planning, implementation, and the following up of an academic quality accreditation project of the department of ( MIS ) in the College of Business (King Khalid University, KSA, 2018-2020). The application of such software will allow improvement, and control participants performance and achievement of the tasks entrusted to them. Also some software components will be added and reused.